Properties of wood polymer composite made from Kenaf (hibicus cannabinus) / Muhamad Zulhilmi Razali - Razali, Muhamad Zulhilmi (Faculty Of Applied Sciences, 2014)
Wood Polymer Composite is a product to increase the interfacial bonding strength between fibers and polymer. The aims of the study are to determine the mechanical properties of Kenaf (Hibicius cannabinus) and to evaluate the best quality strength based from mesh and portion that use as Wood Polymer Composite. Sizes of specimens were 25 mm x 150 mm x 5.77 mm for bending test and 10 mm x 150 mm x 1.77 mm for tensile test. Kenaf fiber specimens were tested for bending and tensile. The results were analyzed based on standard of EN:310:1993 for bending testing and standard EN:319:1993 for tensile testing. ANDVA showed that no significant different in Tensile but there are significant different in Bending. Mesh 60 shows better result than Mesh 40 and core particles portion indicates better strength in both bending and tensile. Kenaf core particles have better potential material for furniture and building component especially tabletop and ceiling.